2018
DOI: 10.3390/molecules23102414
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Poly(Vinyl Alcohol)-Chitosan-Hydroxyapatite Scaffolds: A Promising Alternative for Bone Tissue Regeneration

Abstract: Scaffolds can be considered as one of the most promising treatments for bone tissue regeneration. Herein, blends of chitosan, poly(vinyl alcohol), and hydroxyapatite in different ratios were used to synthesize scaffolds via freeze-drying. Mechanical tests, FTIR, swelling and solubility degree, DSC, morphology, and cell viability were used as characterization techniques. Statistical significance of the experiments was determined using a two-way analysis of variance (ANOVA) with p < 0.05. Crosslinked and plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 90 publications
0
37
0
1
Order By: Relevance
“…The saccharine-related signals are at 1155 and 900 cm −1 [59,60]. The peaks at 1030 and 1080 cm −1 indicate the C–O stretching vibration [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The saccharine-related signals are at 1155 and 900 cm −1 [59,60]. The peaks at 1030 and 1080 cm −1 indicate the C–O stretching vibration [5].…”
Section: Resultsmentioning
confidence: 99%
“…However, natural polymers do not have the appropriate mechanical properties whereas synthetics are deficient in terms of biocompatibility [3]. Thus, in order to overcome the poor performance of natural polymers, bioartificial polymeric materials (BAPMs) have been introduced [4,5,6,7,8]. These combine the biocompatibility of the biological component with the physical and mechanical properties of the synthetic ones [9].…”
Section: Introductionmentioning
confidence: 99%
“…Al romper los puentes de hidrógeno, incrementa la movilidad molecular, y como resultado las películas son más flexibles (M. Chen et al,2018). (Pineda-Castillo et al, 2018); b). Quitosano-glicerol (Sumarni, Prasetya, & Rahayu, 2017) Por lo anteriormente mencionado, en esta investigación se prepararon soluciones ácidas de quitosano y a estas soluciones se les agregó glicerol y ácido láctico (al 0,02% y 0,05% respectivamente).…”
Section: Introductionunclassified
“…The combination of CHI and PVA may have beneficial effects on the biological characteristics of the blend. In fact, it has been reported that the chemical crosslinking between CHI and PVA may improve the mechanical strength and thermal stability, keeping the intrinsic properties of transparency and the swelling ability of CHI films [28,29]. Indeed, the use of plasticizers and crosslinkers imparts specific properties in the system and therefore, their mechanical drawbacks are diminished or attenuated.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is expected that polymers with higher charge densities resulted in an improved antimicrobial activity. Indeed, there are successful studies related to PVA/CHI systems, which show adequate cell viability, non-toxicity, and suitable properties which can be tailored for prospective uses in tissue engineering [19,29,31,32].…”
Section: Introductionmentioning
confidence: 99%